Prenatal maternal organophosphorus pesticide exposures, paraoxonase 1, and childhood adiposity in the Mount Sinai Children's Environmental Health Study. (September 2020) - Etzel, Taylor M.; Engel, Stephanie M.; Quirós-Alcalá, Lesliam; Chen, Jia; Barr, Dana B.; Wolff, Mary S.; Buckley, Jessie P.
Highlights: First study of associations between prenatal OP exposures and child adiposity. No associations observed between prenatal ∑DMP and ∑DEP and child fat mass or BMI. Maternal PON1 genotype may modify associations with child adiposity. Abstract: Background: Animal studies suggest that organophosphorus pesticides (OPs) may be environmental obesogens. While prenatal OP exposures have been associated with altered infant glucose metabolism, associations with pediatric adiposity remain unknown. Methods: We summed concentrations of three dimethylphosphate (∑DMP) and three diethylphosphate (∑DEP) metabolites of OPs measured in third trimester spot urine samples collected from pregnant women enrolled in New York City, 1998–2002. We measured percent fat mass using bio-electrical impedance analysis and calculated age- and sex-standardized body mass index (BMI) z-scores from anthropometric measurements collected at approximately 4, 6, and 7–9 years of age (166 children, 333 observations). We assessed covariate-adjusted associations of OPs with repeated adiposity measures using linear mixed models and evaluated effect measure modification (EMM) by sex and paroxonase ( PON) 1 –108C/T and Q192R polymorphisms measured in maternal peripheral blood samples. Results: The geometric mean urinary concentration of ∑DMP metabolites (29.9 nmol/L, IQR: 105.2 nmol/L) was higher than ∑DEP metabolites (8.8 nmol/L, IQR: 31.2 nmol/L). Adjusted associations were null, with differences in fat mass per 10-fold increase in prenatal ∑DMP and ∑DEP concentrations of 0.7% (95% CI: −0.6, 2.0) and 0.8% (95% CI: −0.4, 2.0), respectively. Maternal PON1 -108C /T polymorphisms modified relationships of prenatal ∑DMP with percent fat mass (EMM p-value = 0.18) and ∑DEP with BMI z-scores (EMM p-value = 0.12). For example, ∑DMP was modestly associated with increased percent fat mass among children of mothers with the at-risk CT or TT genotype (β = 1.2%, 95% CI: −0.6, 3.0) but not among those whose mothers had the CC genotype (β = −0.4%, 95% CI: −2.4, 1.5). Associations were not modified by sex or maternal PON1 Q192R polymorphisms. Conclusions: We observed little evidence of a relationship between prenatal OP exposures and child adiposity, although there was some suggestion of increased risk among offspring of mothers who were slow OP metabolizers. Larger studies are warranted to further evaluate possible associations of prenatal OP exposures with child adiposity and differences by maternal PON1 genotype, which regulates OP metabolism and may increase susceptibility to exposure.